New lower permian (cisuralian) actinopterygians (osteichthyes) from the Pedra do Fogo formation, ne Brazil - Richter, Martha (2016)
To date, only one ray-finned fish has been recorded from the Pedra de Fogo Formation of the Parnaíba Basin in the State of Maranhão, namely Brazilichthys macrognathus, the post-cranium of which isunknown. Here we report on the discovery of three lower actinopterygian taxa from this formation thatare new to science. One of them was collected in the State of Piauí and other two in the State ofMaranhão. One specimen is preserved with an articulated fin and partially articulated squamation. Theother two taxa are preserved as disarticulated dermal scales.Taxon 1 is a large fish with an estimated length of at least 100mm and bearing scales twice as deep asthey are wide. These have a long mid-dorsal peg that articulates with an elongated socket on the innerside of the scale. The non-overlapping outer surface occupies two thirds of the length of the scale andbears numerous round tubercles and longitudinally elongated tubercles. The overlapping area ispractically smooth. Cellular isopedine makes up half to three quarters of the scale thickness. Theornamental tubercles on the scale are made of ganoine-free orthodentine odontodes formingodontocomplexes that were extensively resorbed and redeposited. Taxon 2 is represented by hundreds ofvery elongated, rhombic, palaeoniscoid scales ornamented with strong longitudinal ridges and serratedposterior margins. Most of the flank scales have a strong, often recurved anterior-dorsal process, but aweak or absent peg-and-socket articulation system. In transverse section, the basal bone layer is generallystraight except towards the anterior part of the scale, where it curves up, following the orientation of theanterior articulatory process. Three tissues are present, cellular isopedine at the base, single odontodes aswell as odontocomplexes and thick layers of ganoine with ?pseudo-prismatic? microcrystallineultrastructure. An extensive network of vascular canals crosses the scale mostly from the inner to theouter side. Taxon 3 is a small fish c.120 mm in total length, represented by a pectoral fin showing veryelongated marginal lepidotrichia and poorly preserved squamation. Its scales are as long as they are widewith the outer surface ornamented by longitudinal ridges and the inner side showing a peg-and-socketarticulation.The fishes come from lacustrine mudstones with a rich vertebrate fauna including dipnoans, coelacanths,xenacanth sharks and holocephalians, as well as recently described temnospondyls and captorhinid reptileremains.